Test–retest Reliability and Measurement Error Are Excellent for the Dutch Version of the VascuQol Questionnaire in Patients with Intermittent Claudication. Issue 4 (October 2015) - Conijn, A.P.; Loukachov, V.V.; Bipat, S.; Koelemay, M.J.W.
Abstract : Objectives: Although the Vascular Quality of Life Questionnaire (VascuQol) is a widely used instrument to assess quality of life in patients with peripheral arterial disease (PAD), data on its reliability are scarce and its measurement error is unknown. The aim of this study was to determine test–retest reliability and measurement error of the Dutch version of the VascuQol in patients with intermittent claudication (IC). Methods: Patients with intermittent claudication due to PAD presenting between October 2013 and April 2014 completed the VascuQol twice, with a 1 week interval. Test–retest reliability was expressed as the intraclass correlation coefficient (ICC) with 95% confidence interval (CI), and measurement error as a standard error of measurement (SEM). Results: Sixty-one patients completed two VascuQol questionnaires sufficiently. The ICC for the VascuQol sumscore was 0.91 (95% CI 0.86–0.95). The ICC for the different VascuQol domains ranged between 0.77 (95% CI 0.64–0.86) and 0.87 (95% CI 0.79–0.92). The SEM of the sumscore was 0.34 and ranged between 0.44 and 0.76 for the different VascuQol domains. Conclusions: The test–retest reliability of the Dutch version of the VascuQol is excellent, both for the sumscore and for its different domains. The VascuQol has a measurement error that is sufficiently small to allow detection of clinically relevant changes.